Magnetic adsorbent, preparation method and application thereof, and pretreatment method and detection method of anesthetic in water body

By using the magnetic solid phase extraction technology of the magnetic adsorbent of Fe3O4@PDA as the core, the existing problems of high cost, long time and single detection types of anesthetic residue detection methods in water are solved, and efficient, fast and accurate detection of multiple anesthetics is achieved.

CN119819272APending Publication Date: 2025-04-15ZHEJIANG ACADEMY OF AGRICULTURE SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510081288.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing water anesthetic residue detection methods are costly, time-consuming, require a large amount of organic solvents, and it is difficult to detect multiple anesthetics at the same time.

Method used

The multifunctional magnetic adsorbent based on Fe3O4@PDA as the core was used to pre-treat the sample through magnetic solid phase extraction technology, and the adsorbed material was separated by magnets in one step, simplified the operation process, and was detected in combination with liquid chromatography-tandem mass spectrometry.

Benefits of technology

It greatly simplifies the operation process, improves detection efficiency, reduces the consumption of organic solvents, and can detect multiple anesthetics sensitively at the same time to meet the needs of fast and accurate detection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119819272A_ABST
    Figure CN119819272A_ABST
Patent Text Reader

Abstract

The invention provides a magnetic adsorbent, a preparation method and application thereof, and a pretreatment method and a detection method of an anesthetic in a water body, and belongs to the technical field of analysis and detection. The magnetic adsorbent provided by the invention comprises Fe3O4 (at) PDA, and DVB and NVP which are coated on the surface of the microsphere through polymerization reaction. The magnetic adsorbent is separated in one step by using a magnet, so that centrifugation, column passing and nitrogen blowing are avoided, a pretreatment method of the anesthetic in a water body and an operation process during detection are greatly simplified, the detection efficiency is improved, and the technical problems that an existing method for detecting residual anesthetic in water is tedious in operation, long in consumed time and needs a large amount of organic solvents are solved; the material can be recycled; and the magnetic adsorbent has amphipathy and has high-efficiency adsorption and desorption on two anesthetics, so that the problems of single detection type and incomplete anesthetic detection type of the existing anesthetic residue detection method are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of analysis and detection, and in particular to a magnetic adsorbent and a preparation method and application thereof, and a pretreatment method and a detection method of anesthetics in water. Background Art

[0002] With the improvement of human medical level, the use and residue of drugs have received more extensive attention. Among them, the residues of local anesthetics and benzodiazepine anesthetics are also an important problem. Long-term exposure to anesthetics can cause serious side effects to the human body, and countries have strict management and use of the two types of anesthetics. Therefore, it is necessary to develop a trace detection technology that can detect two anesthetics simultaneously with high sensitivity. At present, liquid chromatography-tandem mass spectrometry is a commonly used method for detecting anesthetic residues, which has the advantages of high sensitivity, high selectivity and high accuracy. The use of this method usually requires a sample pretreatment process, which largely avoids the occurrence of analytical errors.

[0003] The relevant technology is mainly to improve the sample pretreatment method of liquid chromatography-tandem mass spectrometry to improve the detection efficiency. For example, liquid-liquid extraction is used for sample pretreatment to improve the detection efficiency, but there are shortcomings such as high cost, long time consumption, and the need for a large amount of organic solvents; for example, solid phase extraction (SPE) is used for sample pretreatment to further improve the detection efficiency, but it is difficult to recycle the materials for recycling. The solid phase extraction method includes the following steps: column activation, sample extraction, column purification and elution. Before elution, the small amount of water remaining in the column must be driven out as much as possible by vacuuming or blowing in compressed air or nitrogen, otherwise the sample solution obtained later will be diluted. When the eluent is immiscible with water, stratification or emulsification will also occur. The above-mentioned SPE method is a common pretreatment technology for samples in the current anesthetic residue detection. Compared with other sample pretreatment methods, this method is relatively fast, but the operation is cumbersome, and nitrogen blowing is required during elution, which increases the pretreatment time. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a magnetic adsorbent and its preparation method and application, a pretreatment method and a detection method of anesthetics in water. The magnetic adsorbent of the present invention uses a magnet for one-step separation during separation, avoiding centrifugation, column flushing and nitrogen blowing, and greatly simplifying the operation process.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The invention provides a magnetic adsorbent, comprising microspheres and divinylbenzene and N-vinylpyrrolidone coated on the surface of the microspheres through polymerization reaction. The microspheres have a core-shell structure, with Fe3O4 nanoparticles as cores and polydopamine as shells.

[0007] Preferably, the molar ratio of divinylbenzene to N-vinylpyrrolidone is 0:2 to 2:0, and the molar amounts of divinylbenzene and N-vinylpyrrolidone are not zero.

[0008] Preferably, the molar ratio of divinylbenzene to N-vinylpyrrolidone is 1:1, 1:3 or 3:1.

[0009] Preferably, the particle size of the magnetic adsorbent is 200-500 nm, the particle size of the microsphere is 150-400 nm, and the particle size of the Fe3O4 nanoparticles is 50-300 nm.

[0010] The present invention also provides a method for preparing the magnetic adsorbent described in the above technical solution, comprising the following steps:

[0011] Fe3O4 nanoparticles, dopamine and buffer solution were stirred to obtain microspheres;

[0012] The microspheres, divinylbenzene, N-vinylpyrrolidone, an initiator and a solvent are mixed to carry out a polymerization reaction to obtain the magnetic adsorbent.

[0013] Preferably, the mass ratio of the microspheres to divinylbenzene is 3:5 to 3:15.

[0014] Preferably, the polymerization reaction temperature is 70 to 95° C. and the time is 12 to 24 hours.

[0015] The present invention also provides the use of the magnetic adsorbent described in the above technical solution or the magnetic adsorbent prepared by the preparation method described in the above technical solution in the field of adsorbing anesthetics in water.

[0016] The present invention also provides a method for pre-treating an anesthetic in water, comprising the following steps:

[0017] Activating the magnetic adsorbent described in the above technical solution or the magnetic adsorbent prepared by the preparation method described in the above technical solution to obtain an activated adsorbent;

[0018] The activated adsorbent is used to perform magnetic solid phase extraction on a water body to be treated, wherein the water body to be treated contains an anesthetic.

[0019] The present invention also provides a method for detecting anesthetics in water, comprising the following steps:

[0020] Using the pre-treatment method described in the above technical solution, the adsorbed magnetic material is obtained;

[0021] Eluting the adsorbed magnetic material to obtain an eluate;

[0022] The eluate was subjected to liquid chromatography-tandem mass spectrometry detection.

[0023] The invention provides a magnetic adsorbent, comprising microspheres (Fe3O4@PDA) and divinylbenzene (DVB) and N-vinylpyrrolidone (NVP) coated on the surface of the microspheres by polymerization reaction, wherein the microspheres have a core-shell structure, with Fe3O4 nanoparticles as the core and polydopamine as the shell.

[0024] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0025] The magnetic adsorbent of the present invention uses a magnet for one-step separation during separation, avoiding centrifugation, column passing and nitrogen blowing, greatly simplifying the pretreatment method of anesthetics in water and the operating procedures during detection, improving the detection efficiency, solving the technical problems of the existing anesthetic residue detection method in water, which is high in cost, time-consuming and requires a large amount of organic solvent, and the material can be recycled and reused; and the magnetic adsorbent of the present invention is a multifunctional magnetic material based on Fe3O4@PDA as the core, which has amphiphilicity and has high affinity for two types of anesthetics (including caine anesthetics and benzodiazepine anesthetics). Efficient adsorption and desorption (the reason is that NVP has a C=O bond and is a hydrophilic, highly polar modified monomer, while DVB has a symmetrical structure and is a lipophilic, non-polar modified monomer. The combination of the two gives the magnetic adsorbent amphiphilicity, which can adsorb hydrophilic / lipophilic anesthetics at the same time. At the same time, the benzene rings of the two monomers are more likely to form π-π conjugation and other interactions, providing better adsorption performance), which solves the problems of the existing anesthetic residue detection methods of single detection type and incomplete anesthetic detection types, and realizes the rapid and sensitive detection of two types of anesthetics in water.

[0026] The present invention also provides a method for pre-treatment of anesthetics in water, which is a magnetic solid phase extraction (MSPE) technology. The magnetic solid phase extraction method is created using the magnetic adsorbent, and the adsorption material can be separated using a magnet, which greatly shortens the sample pre-treatment time and reduces the consumption of organic solvents. It can also sensitively detect multiple anesthetics at the same time, meeting the needs of rapid and accurate detection.

[0027] The present invention also provides a method for detecting anesthetics in water, which adopts a detection method of magnetic solid phase extraction (MSPE)-liquid chromatography-tandem mass spectrometry (LC-MS / MS), can detect trace drug residues, and can sensitively and quickly detect anesthetics in the range of 0.2 to 40 μg / L. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 SEM images of MAs-1, MAs-2, MAs-3, MAs-4, and MAs-5 and TEM image of MAs-1;

[0029] Figure 2 It is the basic flow chart of specific detection experiment;

[0030] Figure 3 It is a bar graph of the recovery rate of different magnetic adsorbents;

[0031] Figure 4 It is a bar graph of the recovery rate of magnetic adsorbents with different masses;

[0032] Figure 5 It is a bar graph of the recovery rate of magnetic adsorbent after different ultrasonic times;

[0033] Figure 6 It is a bar graph of recovery rate of different eluents;

[0034] Figure 7 This is a bar graph of the water contact angles of Fe3O4@PDA, MAs-1, MAs-2, MAs-3, MAs-4, and MAs-5. DETAILED DESCRIPTION

[0035] The invention provides a magnetic adsorbent, comprising microspheres and divinylbenzene and N-vinylpyrrolidone coated on the surface of the microspheres through polymerization reaction. The microspheres have a core-shell structure, with Fe3O4 nanoparticles as cores and polydopamine as shells.

[0036] In the present invention, the molar ratio of divinylbenzene to N-vinylpyrrolidone is preferably 0:2 to 2:0, and the molar amounts of divinylbenzene and N-vinylpyrrolidone are not 0, and specifically can be 1:1, 1:3 or 3:1; depending on the molar ratio of divinylbenzene to N-vinylpyrrolidone, the amphiphilicity of the obtained magnetic adsorbent will also be different.

[0037] In the present invention, the particle size of the magnetic adsorbent is preferably 200-500nm, specifically 200, 250, 300, 350, 400, 450 or 500nm; the particle size of the microspheres is preferably 150-400nm, specifically 150, 200, 250, 300, 350 or 400nm; the particle size of the Fe3O4 nanoparticles is preferably 50-300nm, specifically 50, 100, 150, 200, 250 or 300nm.

[0038] The present invention also provides a method for preparing the magnetic adsorbent described in the above technical solution, comprising the following steps:

[0039] Fe3O4 nanoparticles, dopamine and buffer solution were stirred to obtain microspheres;

[0040] The microspheres, divinylbenzene, N-vinylpyrrolidone, an initiator and a solvent are mixed to carry out a polymerization reaction to obtain the magnetic adsorbent.

[0041] In the present invention, unless otherwise specified, the raw materials used are all commercially available products in the art.

[0042] The invention stirs Fe3O4 nanoparticles, dopamine and a buffer solution to obtain microspheres.

[0043] In a specific embodiment of the present invention, the preparation process of the Fe3O4 nanoparticles includes the following steps: weighing FeCl3·6H2O, NaCit·2H2O (surfactant), and anhydrous sodium acetate and dissolving them in ethylene glycol respectively (separate ultrasonic dissolution), and after dissolution, magnetically stirring the resulting solution at room temperature for 2 hours to fully mix to obtain a mixed solution, placing the mixed solution in a reactor, reacting at 200°C for 12 hours, magnetically separating the resulting material, and after the waste liquid is poured out, washing the remaining magnetic material with anhydrous ethanol three times and drying at 30°C to obtain the Fe3O4 nanoparticles.

[0044] In the present invention, the buffer solution is preferably a phosphate buffer solution, the pH value of the phosphate buffer solution is preferably 8.5, and the phosphate buffer solution is preferably prepared by a method comprising the following steps: weighing 0.082 g of sodium dihydrogen phosphate and 8.765 g of sodium dihydrogen phosphate, adding 500 mL of pure water, and mixing by ultrasonication.

[0045] In the present invention, the dosage ratio of the Fe3O4 nanoparticles, dopamine and buffer solution is preferably 2g:0.8g:250mL.

[0046] In a specific embodiment of the present invention, the Fe3O4 nanoparticles are preferably weighed and added to a phosphate buffer in a round-bottom flask. After ultrasonication for 20 minutes, the dopamine is added and physically stirred overnight. After the obtained material is magnetically separated and the waste liquid is poured out, the obtained solid is washed 3 times with pure water and 3 times with anhydrous ethanol, and then dried at 50°C to obtain the microspheres.

[0047] After the microspheres are obtained, the microspheres, divinylbenzene, N-vinylpyrrolidone, an initiator and a solvent are mixed to carry out a polymerization reaction to obtain the magnetic adsorbent.

[0048] In the present invention, the mass ratio of the microspheres to divinylbenzene is preferably 3:5 to 3:15, specifically 3:5, 3:9, 3:10, 3:12 or 3:15.

[0049] In the present invention, the initiator is preferably azobisisobutyronitrile.

[0050] In the present invention, the mass ratio of the microspheres to the initiator is preferably 3:0.1.

[0051] In the present invention, the solvent is preferably acetonitrile.

[0052] In the present invention, the dosage ratio of the microspheres to the solvent is preferably 3 g:500 mL.

[0053] In the present invention, the polymerization reaction temperature is preferably 70-95°C, specifically 70 / 75, 80, 85 or 90°C, and the reaction time is preferably 12-24h, specifically 12, 14, 16, 18, 20, 22, or 24h; in the present invention, divinylbenzene and N-vinylpyrrolidone both contain C=C double bonds and can be coated on the Fe3O4@PDA surface through polymerization reaction.

[0054] In the present invention, the polymerization reaction is preferably carried out under a protective atmosphere, and the protective atmosphere is preferably nitrogen.

[0055] In a specific embodiment of the present invention, it is preferred to first weigh the Fe3O4@PDA and dissolve it in acetonitrile, ultrasonicate it for 15 minutes, then add the initiator, and then add the divinylbenzene and N-vinylpyrrolidone, stir for 30 minutes (300 rpm) under a nitrogen atmosphere, and heat the uniform mixture to carry out the polymerization reaction.

[0056] After the polymerization reaction is completed, the present invention preferably separates the obtained material magnetically, washes it with acetone and anhydrous ethanol three times respectively, and then vacuum-dries it overnight to obtain the magnetic adsorbent.

[0057] In the present invention, the vacuum drying temperature is preferably 60°C.

[0058] The present invention also provides the use of the magnetic adsorbent described in the above technical solution or the magnetic adsorbent prepared by the preparation method described in the above technical solution in the field of adsorbing anesthetics in water.

[0059] The present invention also provides a method for pre-treating an anesthetic in water, comprising the following steps:

[0060] Activating the magnetic adsorbent described in the above technical solution or the magnetic adsorbent prepared by the preparation method described in the above technical solution to obtain an activated adsorbent;

[0061] The activated adsorbent is used to perform magnetic solid phase extraction on a water body to be treated, wherein the water body to be treated contains an anesthetic.

[0062] In the present invention, the magnetic adsorbent described in the above technical solution or the magnetic adsorbent prepared by the preparation method described in the above technical solution is activated to obtain an activated adsorbent.

[0063] In the present invention, the activating agent used in the activation preferably includes methanol.

[0064] In the present invention, the dosage ratio of the magnetic adsorbent to the activator is preferably 10 to 70 mg:2 mL, specifically 10 mg:2 mL, 20 mg:2 mL, 30 mg:2 mL, 40 mg:2 mL, 50 mg:2 mL, 60 mg:2 mL or 70 mg:2 mL.

[0065] In the present invention, the activation is preferably performed by standing on a magnet, the activation time is preferably 2 minutes, and the temperature is preferably room temperature.

[0066] After the activation is completed, the present invention preferably places the activated system on a magnet and leaves it to stand for 2 minutes before removing the activator to obtain the activated adsorbent.

[0067] After obtaining the activated adsorbent, the present invention uses the activated adsorbent to perform magnetic solid phase extraction on a water body to be treated, wherein the water body to be treated contains an anesthetic.

[0068] In the present invention, the anesthetic preferably includes a caine anesthetic and a benzodiazepine anesthetic.

[0069] In the present invention, the caine-based anesthetic preferably includes one or more of procaine, lidocaine, tricaine, benzocaine, bupivacaine and tetracaine, and the benzodiazepine-based anesthetic preferably includes one or more of nitrazepam, nimetazepam, triazolam, alprazolam, oxazepam and diazepam.

[0070] In the present invention, the concentration of the anesthetic in the water to be treated is preferably 0.2-100 μg / L, specifically 0.2, 20, 40, 60, 80 or 100 μg / L.

[0071] In the present invention, the dosage ratio of the activated adsorbent to the water to be treated is preferably 20 mg:10-50 mL, specifically 20 mg:10 mL, 20 mg:25 mL or 20 mg:50 mL.

[0072] In the present invention, the activated adsorbent is preferably used to subject the water body to be treated by ultrasonic treatment before the magnetic solid phase extraction is performed.

[0073] In the present invention, the ultrasonic treatment time is preferably 0 to 20 min, specifically 5, 10, 15 or 20 min.

[0074] The present invention also provides a method for detecting anesthetics in water, comprising the following steps:

[0075] Using the pre-treatment method described in the above technical solution, the adsorbed magnetic material is obtained;

[0076] Eluting the adsorbed magnetic material to obtain an eluate;

[0077] The eluate was subjected to liquid chromatography-tandem mass spectrometry detection.

[0078] The present invention utilizes the pre-treatment method described in the above technical solution to obtain the adsorbed magnetic material.

[0079] The present invention preferably separates the supernatant and collects the bottom magnetic material.

[0080] After obtaining the adsorbed magnetic material, the present invention elutes the adsorbed magnetic material to obtain an eluent.

[0081] In the present invention, the eluent for elution is preferably a methanol solution of formic acid or an acetonitrile solution of formic acid. The concentration of formic acid in the methanol solution of formic acid is preferably 0-0.5% (v / v), specifically 0% (v / v), 0.1% (v / v), 0.2% (v / v), 0.3% (v / v), 0.4% (v / v) or 0.5% (v / v). The concentration of formic acid in the acetonitrile solution of formic acid is preferably 0-0.5% (v / v), specifically 0% (v / v), 0.1% (v / v), 0.2% (v / v), 0.3% (v / v), 0.4% (v / v) or 0.5% (v / v).

[0082] In the present invention, the dosage ratio of the adsorbed magnetic material to the eluent is preferably 10 to 70 mg:2 mL, specifically 10 mg:2 mL, 20 mg:2 mL, 30 mg:2 mL, 40 mg:2 mL, 50 mg:2 mL, 60 mg:2 mL or 70 mg:2 mL.

[0083] In the present invention, the elution is preferably carried out under ultrasonic conditions, and the ultrasonic time is preferably 15 minutes.

[0084] After the elution is completed, the present invention preferably separates the magnetic material and the eluent on a magnet in the elution system, and filters the eluent using a 0.22 μm filter membrane.

[0085] After obtaining the eluate, the present invention performs liquid chromatography-tandem mass spectrometry detection on the eluate.

[0086] In the present invention, the parameters of the liquid chromatography-tandem mass spectrometry detection preferably include: using a Luna C18 chromatographic column (100 mm×2.1 mm, 1.7 mm, Waters Corporation, USA); the mobile phase is 0.1% v / v formic acid / 5 mmol·L -1Ammonium acetate water (mobile phase A) and methanol (mobile phase B) were used for elution with a gradient program (relative to the B phase): 40% B (1 min), 80% B (2 min), 95% B (2 min, hold for 2 min), 5% B (0.1 min, hold for 2 min), the total analysis time was 9 min, and the flow rate was 0.3 mL min -1 , the injection volume was 5 μL, and the column temperature was maintained at 35 °C.

[0087] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0088] The detection conditions of LC-MS / MS analysis in the present invention are as follows:

[0089] A Luna C18 column (100 mm × 2.1 mm, 1.7 mm, Waters Corporation, USA) was used; the mobile phase was 0.1% v / v formic acid / 5 mmol·L -1 Ammonium acetate water (mobile phase A) and methanol (mobile phase B) were used for elution with a gradient program (relative to the B phase): 40% B (1 min), 80% B (2 min), 95% B (2 min, hold for 2 min), 5% B (0.1 min, hold for 2 min), the total analysis time was 9 min, and the flow rate was 0.3 mL min -1 , the injection volume was 5 μL, and the column temperature was maintained at 35 °C.

[0090] Example

[0091] 1) Magnetic adsorbent

[0092] A. Synthesis of magnetic adsorbent

[0093] 1. Weigh 13.6g FeCl3·6H2O, 4.0g NaCit·2H2O, and 24g anhydrous sodium acetate and dissolve them in 140, 130, and 130mL ethylene glycol respectively (dissolve by ultrasonic separately). After dissolution, the mixed solution is 400mL in total. After being fully mixed by magnetic stirring for 2h at room temperature, it is placed in a 500mL reactor and reacted at 200℃ for 12h. The material is magnetically separated, and after the waste liquid is poured out, the remaining magnetic material is washed 3 times with anhydrous ethanol and dried at 30℃. The material is marked as Fe3O4 (particle size is 50-300nm).

[0094] 2. Weigh 2.0g of Fe3O4 and add 250mL of phosphate buffer with a pH value of 8.5 (the preparation method is as follows: weigh 0.082g of sodium dihydrogen phosphate and 8.765g of sodium dihydrogen phosphate, add 500mL of pure water, and mix by ultrasonication) in a round-bottom flask. After ultrasonication for 20 minutes, add 0.8g of dopamine and physically stir overnight. After magnetic separation of the material and pouring out the waste liquid, wash it with pure water for 3 times, then wash it with anhydrous ethanol for 3 times, and dry it at 50°C. The material is marked as Fe3O4@PDA (particle size is 150-400nm).

[0095] 3. Weigh 3g Fe3O4@PDA and dissolve it in 500mL acetonitrile, sonicate for 15min, add 0.1g azobisisobutyronitrile, add divinylbenzene (5g) and N-vinylpyrrolidone, and stir for 30min (300rpm) under nitrogen atmosphere. Heat the homogeneous mixture to 75℃ and perform polymerization for 16h. Separate the material magnetically, rinse with acetone and anhydrous ethanol three times, and vacuum dry at 60℃ overnight. The materials are labeled as MAs1~5. (The molar ratio is MAs-1=0:0.1, MAs-2=0.025:0.075, MAs-3=0.05:0.05, MAs-4=0.075:0.025, MAs-5=0.1:0, (NVP:DVB) mol / mol; the particle size of MAs is 200~500nm).

[0096] Both DVB and NVP contain C=C double bonds, which can be coated on the surface of magnetic Fe3O4@PDA through polymerization reaction. The amphiphilicity of the final product will be different according to the different monomer ratios during synthesis. The amphiphilicity is characterized by water contact angle, see Figure 7 The synthesized magnetic adsorbent was characterized by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Figure 1 , Figure 1 The SEM images of MAs-1, MAs-2, MAs-3, MAs-4, and MAs-5 and the TEM image of MAs-1 show that the synthesized magnetic adsorbent is a spherical particle with a core-shell structure. The dispersibility of the magnetic adsorbent decreases with the increase of the NVP monomer ratio, because the hydrophilic monomer NVP easily forms hydrogen bonds, making the magnetic adsorbent containing more NVP monomers more likely to aggregate together. On the contrary, the magnetic adsorbent containing only DVB monomers hardly aggregates. The dispersibility of MAs-3 is moderate, and it is obviously present in the form of microspheres.

[0097] B. Optimization of the ratio of magnetic adsorbent monomers

[0098] Accurately weigh 50 mg of magnetic adsorbent (MAs1, MAs2, MAs3, MAs4, MAs5) in a 100 mL beaker, add 2 mL of methanol to activate it, place it on a magnet and let it stand for 2 minutes to remove the methanol, add 50 mL of pure water with mixed standards (the concentration is 20 μg / L, the preparation steps are as follows: add 100 μL, 10 μg / L mixed standard mother liquor to pure water), and ultrasonicate for 15 minutes. After the ultrasonication, place the beaker on the magnet and let it stand, waiting for the magnetic material to be completely adsorbed on the bottom of the beaker, separate the supernatant and collect the magnetic material at the bottom. Add 2 mL of eluent (0.5% v / v formic acid in methanol solution) to the separated magnetic material to elute the magnetic material. After ultrasonication for 30 seconds, place the beaker on a magnet to separate the magnetic material and the eluent, take 1 mL of the eluent and filter it with a 0.22 μm filter membrane, and enter LC-MS / MS analysis. The basic flow chart of the specific detection experiment is as follows: Figure 2 The recovery results are shown in Figure 3 . The results showed that the adsorption efficiency of most anesthetics by magnetic adsorbents without DVB monomers was very low. As the proportion of NVP monomers increased, the recovery rates of various anesthetics increased. When the proportion of NVP exceeded half, the adsorption efficiency of the magnetic adsorbent for each anesthetic changed slightly. Taking all factors into consideration, MAs-3 (DVB:NVP=0.05:0.05, mol / mol) recovered the lowest procaine and achieved the maximum recovery rate, and the recovery rates of other anesthetics did not decrease significantly. Therefore, MAs-3 was selected for subsequent research.

[0099] 2) Optimization of extraction process

[0100] Accurately weigh different masses (10, 20, 30, 40, 50, 60 and 70 mg) of magnetic adsorbent MAs-3 in a 100 mL beaker, add 2 mL of methanol to activate, place on a magnet and let stand for 2 min to remove the methanol, add 50 mL of pure water with mixed standard (concentration is 20 μg / L, the preparation steps are as follows: add 100 μL, 10 μg / L mixed standard mother liquor to pure water), and ultrasonicate for different times (0 min, 5 min, 10 min, 15 min, 20 min). After the ultrasonication, place the beaker on the magnet and let it stand, wait for the magnetic material to be completely adsorbed on the bottom of the beaker, separate the supernatant and collect the magnetic material at the bottom. Add 2 mL of methanol to the separated magnetic material to elute the magnetic material. After ultrasonication for 30 s, place the beaker on a magnet to separate the magnetic material and the eluent, take 1 mL of the eluent and filter it with a 0.22 μm filter membrane, and enter LC-MS / MS analysis. Figure 4 The recovery bar graph of magnetic adsorbents of different masses after 10 minutes of ultrasound treatment is shown in Figure 2. Figure 5The recovery rate of 20 mg magnetic adsorbent after different ultrasonic times is a bar graph. The results show that when the amount of magnetic material is greater than 20 mg, the recovery rate decreases slightly with the increase in the amount of magnetic adsorbent. When the amount of magnetic adsorbent is 20 mg, the recovery rate is between 60% and 120%, which meets the detection requirements; the best recovery rate is achieved when the ultrasonic time is 10 minutes, and there is no need to increase the additional ultrasonic time. Therefore, the present invention selects a 20 mg magnetic adsorbent dosage and an adsorption ultrasonic time of 10 minutes for subsequent research.

[0101] 3) Optimization of elution process

[0102] Accurately weigh 10 mg of magnetic adsorbent MAs-3 in a 100 mL beaker, add 2 mL of methanol to activate it, place it on a magnet and let it stand for 2 minutes, then remove the methanol, add 50 mL of pure water with mixed standard (concentration is 20 μg / L, the preparation steps are as follows: add 100 μL, 10 μg / L mixed standard mother solution to pure water), and ultrasonicate for 10 minutes. After the ultrasonication, place the beaker on the magnet and let it stand until the magnetic material is completely adsorbed on the bottom of the beaker, separate the supernatant and collect the magnetic material at the bottom. Add 2 mL of eluent (methanol, 0.1% v / v formic acid in methanol, 0.5% v / v formic acid in methanol, acetonitrile, 0.1 v / v% formic acid in acetonitrile, 0.5% v / v formic acid in acetonitrile) to the separated magnetic material to elute the magnetic material. After ultrasonication for 30 seconds, place the beaker on a magnet to separate the magnetic material and the eluent. Take 1 mL of the eluent and filter it with a 0.22 μm filter membrane for LC-MS / MS analysis. The recovery results are shown in Figure 2. Figure 6 The results showed that the elution effect of methanol was generally higher than that of acetonitrile, and with the change of acidity, the recovery rate of a small number of target substances increased slightly, while the recovery rate of most target substances decreased slightly. Methanol was selected for subsequent research after comprehensive consideration.

[0103] 4) Recovery and precision

[0104] Pure water was used as the matrix for the addition recovery experiment, and the addition level and results are shown in Table 1. All 12 anesthetics were detected, and except for procaine and 40 μL / L oxazepam, the recovery rates of the remaining anesthetics were between 66.0% and 97.2%, and the RSD was less than 10%. It can be seen that the pretreatment process of the method of the present invention is simple to operate, the results are reliable, and the repeatability is good, and it is suitable for the analysis of trace residue detection of multiple anesthetics in environmental water samples.

[0105] Table 1 Recovery of anesthetics at different addition levels (n=3)

[0106]

[0107] In summary, the present invention proposes a multifunctional magnetic adsorbent based on Fe3O4@PDA as the core. The material is amphiphilic and has high-efficiency adsorption and desorption of two anesthetics, which greatly improves the adsorption efficiency of Fe3O4@PDA for multiple anesthetics. Based on the magnetic adsorbent, a set of common detection and analysis methods (pretreatment methods, instrumental analysis methods) for trace drug residues of multiple anesthetics in environmental water are established. For the first time, MSPE is used to jointly detect two types of anesthetics in environmental water samples, and magnets are used to separate the adsorption materials, which greatly shortens the sample pretreatment time and reduces the consumption of organic solvents. It can sensitively detect multiple anesthetics at the same time, meet the needs of rapid and accurate detection, and can sensitively and quickly detect anesthetics in the range of 0.2 to 40 μg / L.

[0108] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A magnetic adsorbent, characterized in that: The invention comprises microspheres and divinylbenzene and N-vinylpyrrolidone coated on the surface of the microspheres through polymerization reaction. The microspheres have a core-shell structure, with Fe3O4 nanoparticles as cores and polydopamine as shells.

2. The magnetic adsorbent according to claim 1, characterized in that The molar ratio of the divinylbenzene to N-vinylpyrrolidone is 0:2 to 2:0, and the molar amounts of the divinylbenzene and N-vinylpyrrolidone are not zero.

3. The magnetic adsorbent according to claim 2, characterized in that: The molar ratio of divinylbenzene to N-vinylpyrrolidone is 1:1, 1:3 or 3:

1.

4. The magnetic adsorbent according to claim 1, characterized in that: The particle size of the magnetic adsorbent is 200-500 nm, the particle size of the microsphere is 150-400 nm, and the particle size of the Fe3O4 nanoparticle is 50-300 nm.

5. The method for preparing the magnetic adsorbent according to any one of claims 1 to 4, characterized in that: The following steps are involved: Fe3O4 nanoparticles, dopamine and buffer solution were stirred to obtain microspheres; The microspheres, divinylbenzene, N-vinylpyrrolidone, an initiator and a solvent are mixed to carry out a polymerization reaction to obtain the magnetic adsorbent.

6. The preparation method according to claim 5, characterized in that: The mass ratio of the microspheres to divinylbenzene is 3:5 to 3:

15.

7. The preparation method according to claim 5, characterized in that: The polymerization reaction temperature is 70-95° C. and the reaction time is 12-24 hours.

8. Use of the magnetic adsorbent according to any one of claims 1 to 4 or the magnetic adsorbent prepared by the preparation method according to any one of claims 5 to 7 in the field of adsorbing anesthetics in water.

9. A method for pre-treating an anesthetic in water, characterized in that: The following steps are involved: Activating the magnetic adsorbent according to any one of claims 1 to 4 or the magnetic adsorbent prepared by the preparation method according to any one of claims 5 to 7 to obtain an activated adsorbent; The activated adsorbent is used to perform magnetic solid phase extraction on a water body to be treated, wherein the water body to be treated contains an anesthetic.

10. A method for detecting anesthetics in water, characterized in that: The following steps are involved: Using the pre-treatment method of claim 9, obtaining the adsorbed magnetic material; Eluting the adsorbed magnetic material to obtain an eluate; The eluate was subjected to liquid chromatography-tandem mass spectrometry detection.